Influence of the nano hydroxyapatite powder on thermally sprayed HA coatings onto stainless steel - Kulpetchdara K. (2017)
© 2016 Elsevier B.V. The nano Hydroxyapatite (HA) powder was derived from a novel peroxide-based route (PBR) using calcium nitrate, phosphoric acid and hydrogen peroxide as peroxo-precursor. In present work, the effect of nano HA powder on the microstructure and properties of thermally sprayed HA coatings was investigated. The obtained powders were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRD pattern of hydroxyapatite powder corresponded to that of hydroxyapatite and tricalcium phosphate. The nano HA powder was then deposited onto stainless steel substrates using High Velocity Oxy-Fuel (HVOF) method. The influence of the crystallization was evaluated by XRD and SEM. Mechanical property in terms of hardness and bioactivity of the coatings were investigated by Vickers micro hardness testing and soaking in simulated body fluid (SBF), respectively. The results showed that the HA coatings were a mixture of amorphous and crystalline phase. The hardness value of 2.15 ± 0.08 GPa was obtained for the synthesized HA powder coating (SHAC). After soaking in SBF for 14 days, the layer formation of apatite could be observed.